Efektivitas Perencanaan Berdasarkan Nomenklatur Perangkat Daerah Studi Kasus Pada Dinas Tanaman Pangan, Hortikultura Dan Peternakan Kabupaten Lahat - Nisma Aprini; Alfatah Dwi Putera; Marko Ilpiyanto (UNIVED Press, 2023)
This study aims to determine the effectiveness of planning based on the nomenclature of the regional apparatus as well as the supporting and inhibiting factors faced in its application at the Department of Food Crops, Horticulture and Animal Husbandry. This study uses qualitative research methods based on theories/opinions according to experts and the existing literature. The results of the study show that the change in nomenclature based on the Minister of Home Affairs Decree Number 50 of 2020 is in the regional development mission so that the expected effectiveness is significant, but the facts found at the Food Crops, Horticulture and Livestock Service Office of Lahat Regency show the ineffectiveness of planning after the nomenclature change.